2020
DOI: 10.3389/fmolb.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

3D Co-culture of hiPSC-Derived Cardiomyocytes With Cardiac Fibroblasts Improves Tissue-Like Features of Cardiac Spheroids

Abstract: Both cardiomyocytes and cardiac fibroblasts (CF) play essential roles in cardiac development, function, and remodeling. Properties of 3D co-cultures are incompletely understood. Hence, 3D co-culture of cardiomyocytes and CF was characterized, and selected features compared with single-type and 2D culture conditions. Methods: Human cardiomyocytes derived from induced-pluripotent stem cells (hiPSC-CMs) were obtained from Cellular Dynamics or Ncardia, and primary human cardiac fibroblasts from ScienCell. Cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 72 publications
(90 reference statements)
5
116
0
Order By: Relevance
“…We confirm that CFs significantly increased the integrity and synchronized contractility of human cardiac microtissues. As recently demonstrated, the use of a 4:1 ratio (iCMs:CFs) results in cardiac microtissues with stable phenotype and beating properties for up to one month [16]. Our data further demonstrated that contractility of these cardiac microtissues was substantially affected under profibrotic condition (i.e., in the presence of TGF-β1).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We confirm that CFs significantly increased the integrity and synchronized contractility of human cardiac microtissues. As recently demonstrated, the use of a 4:1 ratio (iCMs:CFs) results in cardiac microtissues with stable phenotype and beating properties for up to one month [16]. Our data further demonstrated that contractility of these cardiac microtissues was substantially affected under profibrotic condition (i.e., in the presence of TGF-β1).…”
Section: Discussionsupporting
confidence: 82%
“…Using human iPSC-derived cardiomyocytes (iCMs) and human foetal cardiac fibroblasts (fCFs), we developed a high throughput in vitro model of human cardiac tissue [16]. Cardiac microtissues consisting of 5000 cells each were generated by self-assembly ( Figure S1).…”
Section: Cardiac Fibroblasts Improve Integrity and Contractility Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…hiPSC-CMs lack a fully mature phenotype, and transcriptional progression throughout differentiation renders them most comparable to early-/mid-gestation fetal CMs 3234 . Several key environmental parameters have been implicated in promoting the developmental phenotype of hiPSC-CMs, such as three-dimensional culture 3538 , biochemical cues 3941 , electromechanical stimulation 37,38,4245 , and extended culture duration 4648 . Consistent with previous studies, the cardiac microtissues examined here exhibited overall improvements in calcium handling properties (amplitude, maximum upstroke and downstroke velocities) with prolonged (30 day) culture in the engineered 3D platform.…”
Section: Discussionmentioning
confidence: 99%
“…In these formats they are promising as drug screening platforms due to their superior predictability and physiological structure and function when compared to traditional monolayer cultures [7][8][9][10] . Indeed, the organotypic cell densities in spheroids enhances the cell-cell and cell-extracellular matrix (ECM) interactions that are required to maintain cellular differentiation and phenotype, whereas these interactions are limited in traditional 2D cultures [11][12][13][14] . High cell-densities are necessary to accurately recapitulate many pathological disease states such as cancer or fibrosis where perturbed cell-cell and cell-ECM interactions are central to disease progression.…”
Section: Introductionmentioning
confidence: 99%